VORTEX (Variscite origin recognition technology X-ray based) Data. A European geoarchaeological green phosphate compositional datasetZenodo - Daniel Sánchez-Gómez; José Ángel Garrido-Cordero; José María Martínez-Blanes; Rodrigo Villalobos García; Manuel Edo i Benaiges; Ana Catarina Sousa; María Dolores Zambrana Vega; Ferran Borrell; Rosa Barroso Bermejo; Primitiva Bueno Ramírez; Carlos P. Odriozola (Data in Brief)
This dataset includes the compositional information of n = 1778 geoarchaeological samples of green phosphate minerals sourced from three major Iberian deposits with evidence of prehistoric mining: Aliste, Terena, and the Gavà Mines. It has been used to develop a data-driven framework that integrates portable X-ray fluorescence (p-XRF) analysis and machine learning (ML), to determine the provenance of archaeological artifacts based on its elemental composition. In addition, a mineralogical analysis by X-ray diffraction (XRD) of a subset (N = 249; n_Aliste = 122, n_Terena = 47, n_Gavà = 80) was conducted to complement the geochemical characterisation of the sample. Data from n = 571 variscite beads from 15 Iberian and French archaeological sites, representing a diverse range of chrono-cultural contexts spanning from the Neolithic to the Bronze Age, used to test the model are also presented.The compositional data was obtained by using a portable XRF analyser and is presented as atomic percentages of the elements between Al and Th. Mineral compositions were determined using a Panalytical X’Pert Pro θ/θ diffractometer. This dataset has high reuse potential for future non-destructive studies of archaeological artefacts and past social network analyses.